The Relationship Between Gadget Usage and Learning Concentration Among Students of UIN Syahada Padangsidimpuan - Febrina, Febrina; Harahap, Yuni Patima; Rafi, Syah Zehan; Amelia, Rizky; Fadhilah, Nahdhah (Madiha Press, 2026)
This study explores the relationship between gadget usage and learning concentration among students at UIN SYAHADA. The increasing reliance on digital devices has raised concerns regarding its impact on students’ academic focus and cognitive performance. The primary purpose of this research is to analyze whether high-frequency gadget usage correlates with lower levels of concentration during learning activities. A quantitative research method was applied, using a correlational approach. Data were collected through questionnaires distributed to a sample of 100 students selected using purposive sampling. The results reveal a significant negative correlation between the intensity of gadget usage and students’ concentration in learning. This indicates that students who use gadgets excessively tend to have reduced concentration, which can hinder academic performance. The findings emphasize the importance of promoting balanced gadget use and implementing strategies for digital discipline among students. This study provides insights for educators and policymakers to design interventions that foster healthier learning environments and minimize distractions caused by digital technologies.